Rapid and sensitive microbial analysis by capillary isotachophoresis with continuous electrokinetic injection under field amplified conditions. Issue 11 (18th February 2013) - Phung, Sui Ching; Nai, Yi Heng; Powell, Shane M.; Macka, Mirek; Breadmore, Michael C.
Abstract : A highly sensitive capillary isotachophoresis method with LIF detection for microbial analysis was developed. This allowed the reliable analysis of Escherichia coli bacteria with a LOD of 14 cells in a sample volume of 100 μL, or 1.35 × 10 2 cell/mL, which is 47 times lower than reported by CE‐LIF and 148 times lower than CE‐UV with on‐line concentration. A leading electrolyte of 50 mM Tris‐HCl was used while the cells were diluted in 5 mM Tris HEPES as the terminator. To facilitate detection, cells were stained with the universal nucleic acid fluorophore SYTO 9. Continuous electrokinetic injection of the cells from the terminator under field amplified conditions concentrated cells into a single peak at the leader/terminator boundary allowing quantitation by measurement of peak height. The method was applied to water collected from two local streams, with only filtration through a 5‐μm syringe filter to remove large particulate matter followed by a ten times dilution in terminator, with total analysis time approximately 40 min. The detected cell numbers in the water samples by the isotachophoresis method were 3.70 × 10 5 cell/mL and 2.62 × 10 4 cell/mL, which were slightly higher than the 9.50 × 10 4 cell/mL and 1.96 × 10 4 cell/mL obtained by conventional microbiological plate counting.